Complete Characterization of Molecular Dynamics in Ultrashort Laser Fields - Feuerstein, B.; Ergler, Th.; Rudenko, A.; Zrost, K.; Schröter, C. D.; Moshammer, R.; Ullrich, J.; Niederhausen, T.; Thumm, U. (My University, 2007)
Reaction Microscope-based, complete, and time-resolved Coulomb explosion imaging of vibrating and dissociating D+2 molecules with femtosecond time-resolution allowed us to perform an internuclear distance (R-)dependent Fourier analysis of the corresponding wave packets. Calculations demonstrate that the obtained two-dimensional R-dependent frequency spectra enable the complete characterization of the wave packet dynamics and directly visualize the field-modified molecular potential curves in intense, ultrashort laser pulses.